The Importance of Using Interactive Methods in Improving Students' Historical Analysis and Independent Thinking Skills in the Educational Process (Eurasian Journal of Learning and Academic Teaching, 2022)
There is talk about educating young people as initiative people, getting them used to nonstandard thinking, achieving high results in a short time without spending excessive mental and physical effort.